PENGEMBANGAN ALAT UKUR KEBERSYUKURAN MAHASISWA MUSLIM - Halimatussa'diah Halimatussa’diah; Satriani Satriani; Muthia Muslimah Almi; Yang Dini Azkarisa; Milya Zakiyah (Proyeksi: Jurnal Psikologi, 2020)
the moslim gratitude scale for college students was developed based on aspects devided into items that were tested on 132 Moeslim College students (35 men and 97 women) with an age range beetwen 18 - 30 years old by testing the validity and reliability of the scale. Factor analysis used is exploratory factor analysis (EFA), which was extracted by looking at the value of the Barlett Test of Sphericity = 455.929 with a significance level of 0.000 which means there is a significant correlation between variables. The KMO calculation result of 0.830 shows that the adequacy of the sample is in the upper category. The reliability if the item based on Chronbach Alpha value obtained is 0.851 with the corrected item-total correlation moving value from 0.413 - 0.608, where the gratitude measurement tool is reliable.